Comparative evaluation of antibody response in goats vaccinated with saponin and saponin-al-gel Mycoplasma mycoides subsp capri vaccines by enzyme linked immunosorbent assay - MEHRA, SOMYA; RANA, RAJNEESH; MANDAL, AJOY; KUMAR, VIJAY; KUMAR, ASHOK; VIHAN, V S; SHARMA, M C (The Indian Journal of Animal Sciences, 2011)
In the present study a comparative evaluation was made of antibody response in goats vaccinated with saponin and saponin al-gel Mycoplasma mycoides subsp capri vaccines by ELISA. The inference can be made with the study that vaccine B (saponinâ€“algel) is found to be a superior candidate in raising significantly higher antibody titre in goats as comparison to vaccine A (saponin), although the protein concentration of Mmc antigen in both the preparation was 1.5 mg/dose.Â